Strategies for Building the Image of Islamic Educational Institutions to Attract Public Interest: A Multi-Perspective Study - Yasin, Muhamad (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2023)
This article aims to examine the school’s efforts to build its image to increase public interest. Determining the right choice of school for a child is the task of the community as prospective parents of students. Quality schools will certainly be sought after by the community, including elementary schools. Moreover, schools that have a good image with plus values such as Islamic education institutions that have advantages in general and religious education curricula. The concept of Islamic full day school applied by the school is proven to be able to build a good image of the school, so that it can attract public interest. For this reason, it becomes interesting to examine the success of the primary school work. The approach used in this research is qualitative with the type of case study research, while the data source can be collected directly with a natural setting. This article concludes that to build its image, the school made five efforts: doing promotion so that schools can be more widely known by intensifying and extending school publications; creating competitive advantages in terms of service quality; managing facilities and infrastructure; managing teachers; and manage curriculum. These efforts have proven to increase public interest in sending their children to this elementary school.